Analisis Besarnya Kredit Bermasalah Selama Masa Pandemi Covid-19 pada Perusahaan Financial Technology (FINTECH) - Aris Munandar; Alwi Alwi; Nurhayati Nurhayati; Herman Herman (Universitas Mercu Buana, 2021)
This study aims to determine and analyze the amount of non-performing loans in Financial Technology (FINTECH) companies during the covid-19 pandemic. The research sample consisted of 12 samples from January 2020 - December 2021 with the purposive random sampling method. Data collection is done through the official website of the financial services authority and the type of data taken is secondary data. The results show that non-performing loans in Financial Technology (FINTECH) companies have an average Non-Performing Loan (NPL) value of 6.08%, which is greater than 5% of the maximum limit set. Where these conditions indicate that non-performing loans in Financial Technology (FINTECH) companies are problematic or unhealthy. The increase in non-performing loans began to increase in April 2020 after the COVID-19 outbreak began in Indonesia.